COOKING CLASS SEBAGAI PAKET WISATA DI RESTORAN LAKA LEKE UBUD BALI - Nugraha S., M. Rizky; Sendra, I Made; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 3 No 1 (2015): Jurnal IPTA (July 2015)DO - 10.24843/IPTA.2015.v03.i01.p06)
Selection of research on "Cooking Class as Tour Packages at the Restaurant Laka Leke in Ubud Bali" is motivated the potential that cant be find anything in Ubud area which can be put into a package "cooking class", and how to plan a tour package "cooking class" in support of the potential that exists in Ubud. Data collection in this study was done by observation, interviews, and library research. Type of data used is the qualitative data supported by quantitative data, while the data source are the primary data and secondary data. Results of this study showed that of the observations made on potentiality of tourism in Ubud village is still a lot of potentials that has not been developed and the maximum attention, especially from the local government. Development of tourism in Ubud village just focus on a few places in the Ubud area. For the Bureau of Tourist’s Travel or restaurant should pay more attention to making travel packages which involving local communities and make a package that is unique and different so will not appear tour packages that already exist.
Keywords: Package, Cooking Class, Ubud